Risk Factors for Major Adverse Events after Surgical Closure of Ventricular Septal Defect in Patients Less than 1 Year of Age: A Single-Center Retrospective - Ergün,Servet (2019)
Abstract Objective: To reveal the risk factors that can lead to a complicated course and an increased morbidity in patients < 1 year old after surgical ventricular septal defect (VSD) closure. Methods: We reviewed a consecutive series of patients who were admitted to our institution for surgical VSD closure who were under one year of age, between 2015 and 2018. Mechanical ventilation (MV) time > 24 hours, intensive care unit (ICU) stay longer than three days, and hospital stay longer than seven days were defined as “prolonged”. Unplanned reoperation, complete heart block requiring a permanent pacemaker implantation, sudden circulatory arrest, and death were considered as significant major adverse events (MAE). Results: VSD closure was performed in 185 patients. The median age was five (1-12) months. There was prolonged MV time in 54 (29.2%) patients. Four patients (2.2%) required permanent pacemaker implantation. Hemodynamically significant residual VSD was observed in six (3.2%) patients. Extracorporeal membrane oxygenation-cardiopulmonary resuscitation was performed in one (0.5%) patient. Small age (< 4 months) (P-value<0.001) and prolonged cardiopulmonary bypass time (P=0.03) were found to delay extubation and to prolong MV time. Low birth weight at the operation was associated with MAE (P=0.03). Conclusion: Higher body weight during operation had a reducing effect on the MAE frequency and shortened the MV duration, ICU stay, and hospital stay. As a conclusion, for patients who are scheduled to undergo VSD closure, body weight should be taken into consideration.